The development of the Fungal Resources Conservation System «One District, One Herbarium and Five Banks» and its application on Qinghai-Tibet Plateau - Yu Li; Qi Wang (Аграрная наука Евро-Северо-Востока)
Biodiversity is closely related to human health and ecological environment. It has become very important due to its influence on the economic and political strategies of various countries. Fungal diversity is an important part of biodiversity and is of great significance in maintaining the balance of ecosystems. On the basis of fungal diversity studies the innovative conservation system “One district, one herbarium and five banks” was proposed and later applied on Qinghai-Tibet Plateau. In order to protect important fungal resources a conservation district of Yajiang Matsutake Reserve was established  in Sichuan Province. To preserve the species, genetics and local natural fungal resources, the herbarium, the spawn bank, the viable tissue bank, the gene bank, the compound bank, and the comprehensive information bank were created, which resulted in the systematic protection of fungal diversity on Qinghai-Tibet Plateau and provided support for the sustainable use of fungi. Innovation and integration of the protection system of fungal resources and key technologies for sustainable utilization not only restore the ecological environment of important wild Fungal resources but also screen and cultivate new varieties of edible and medicinal fungi It has been promoted and demonstrated and gave significant ecological, social and economic benefits.